Navigating complexity: The importance of design-based research for faculty development. (3rd April 2021) - Chen, Weichao; Sandars, John; Reeves, Thomas C.
Abstract: Despite the importance of evidence-based medical education, navigating the complexity of its implementation can be frustrating. Faculty development that engages and supports medical educators in Design-Based Research is one promising approach to respond to this challenge. An essential aspect of this process is to expand faculty's Zone of Generativity and thus foster their individual and collective capabilities to navigate the complexity of implementing evidence-based medical education.